Strategic design of conjugated polymer materials for sensors and solid-state lighting - Fox, Niamh Willis (Trinity College (Dublin, Ireland). School of Chemistry, 2016)
Conjugated polymers (CPs) have shown extreme promise in a range of applications such as optical sensors and light-emitting devices due to their exceptional optoelectronic properties, low cost and solution processability. CPs are particularly sought after as sensory materials due to their property of amplified quenching, which can facilitate analyte detection at nanomolar concentrations. This work begins by examining the use of a polyfluorene (blue-emitting)- polythiophene (red-emitting) diblock CP with complementary optoelectronic properties attributed to both blocks, which enables fluorimetric and colorimetric detection of biologically important nucleotides. The magnitude of the optical response is sensitive to both nucleotide geometry and charge. The proposed mechanism behind this process involves electron transfer from the nucleobase to the polythiophene block, mediated by the CP triplet state. Although the vast majority of CP-based sensing schemes involve the detection of electronpoor analytes by electron-rich polymers, there are relatively few examples describing the contrary scenario, electron-rich analyte detection by electron-poor polymers. In Chapter 4, the possibility of increasing the discriminatory action of such electron-poor CP sensor systems through the creation of polyrotaxane species is investigated, whereby macrocycles of differing sizes are exploited to control the effective volume in which the CP and analytes interact. This system may be deposited into the solid-state, whilst retaining its sensing properties to gas phase analytes. The lifetime of any solid-state CP-based device is limited by the photo- and thermal instability of the CP. Incorporation of CPs into an inorganic host allows modulation of the optical properties and aggregation state of the CP, whilst simultaneously improving the environmental stability. However, due to the chemical incompatibility of the two components, inhibiting phase separation across all length scales can be challenging. In Chapters 5-7, the potential of di-ureasil hybrids, comprised of an organic polyether grafted onto a siliceous network via urea linkages, as host materials for CPs is investigated. Firstly, blue-emitting polyfluorene-phenylene CPs were physically immobilised into the di-ureasil to form a Class I hybrid. Examination of the optical properties indicated that both the CPs and the di-ureasil host contribute to the photoluminescence properties giving rise to a dramatic enhancement of the photoluminescence quantum yield (PLQY) to ~60%. This is due to effective prevention of CP aggregation by the di-ureasil host and efficient energy transfer between the two components. Subsequent inclusion of the red-emitting CPs, MEHPPV and P3TMAHT, was carried out in an effort to extend the emission colour from the inherent blue emission of the di-ureasil host across the visible spectrum. The emission colour of these samples was found to be tunable across the blue-white-yellow spectral region due to incomplete Förster resonance energy transfer from the di-ureasil to the CP. Finally, as the properties of such organic-inorganic hybrid materials depend on the interface between the two phases, a polyfluorene was covalently-grafted directly to the siliceous network of a di-ureasil. Energy transfer between the di-ureasil and the CP was observed leading to an improved PLQY when compared to a thin film of the pure CP. On comparison with the physically immobilized samples previously discussed, the magnitude of energy transfer was found to be reduced for the grafted species. This suggests a reduced interaction between the CP and organic component of the di-ureasil, highlighting the ability to further control the interactions between the CP and di-ureasil through careful selection of the incorporation method. The power of the approach presented in this thesis lies in both its simplicity and versatility. Incorporation within a di-ureasil host has showed improved thermal and photostability for each of the CPs investigated. The electronic coupling between the CPs and the di-ureasil suggests that CPdi-ureasils also offer a wealth of potential applications from composite photovoltaics, to luminescent solar concentrators and optical sensors. While the confinement of the CP within a specific region of an active layer offers the potential to reduce the complexity of multi-layer device architectures and may yield improved device performance.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin